Cycle of violence and risk factors. Case studies - Francis Bone, Mónica Alexandra (2023)
The cycle of violence is a repetitive structure of dysfunctional affective couple interaction, a sum of negative emotions that inhibits the woman victim of violence from making assertive decisions regarding her personal development and life-time plans. In this paper we will discuss its construction from the perspective of male-oriented violence and, without pretending to justify it, we will explain the violent behavior, the relationship of this cycle and risk factors to which women victims of violence are exposed, taking as a reference an interview conducted within a scientific research process (doctoral thesis), for which the respective informed consent was obtained.